Skin treatment of non-neoplastic lesions of the bile duct - Bermúdez Villegas, Jorge; Veirano, Gustavo (Cirugía del Uruguay, 1990)
Alter analyzing the causes of anal incondnence and revising its medica/ and surgical treatments the authors present their experience on 64 patients and 62 operations. They point out direct repair alter obstetric section as the one that offers the best results, the suppression of the cause in anal incontinence secondary to other pathologies, and Jevators' postanal repair, which offers a va/id (though with variable results) alternativa in idiopatic anal incontinence or in the one due to perineal descent.